2018
DOI: 10.1213/ane.0000000000002778
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch 130/0.4 and Its Impact on Perioperative Outcome: A Propensity Score Matched Controlled Observation Study

Abstract: An association between intraoperative HES therapy and postoperative kidney failure was not observed in a mixed cohort of elective surgical patients. In addition, HES 130/0.4 was not associated with an increased morbidity or the need for ICU therapy in this propensity score matched study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As most of the negative effects of HES reported in the RCTs involved patients with sepsis, in 2013 European medicines authorities requested further studies evaluating the safety and efficacy of HES in perioperative non-septic patients (86). Several smaller studies and RCTs in non-septic patients in the perioperative setting found no evidence of a nephrotoxic effect of HES (87,88). Likewise, two recent larger, multicenter trials in 4,545 ("RaFTinG" in 2018) and 775 ("FLASH" in 2020) surgical patients also found no significant difference in mortality between patients who received HES or crystalloids and AKI in one (89), and according to the authors a reduced risk of RRT and AKI in another (90) (Supplementary Table 1).…”
Section: Acute Kidney Injury and Mortalitymentioning
confidence: 99%
“…As most of the negative effects of HES reported in the RCTs involved patients with sepsis, in 2013 European medicines authorities requested further studies evaluating the safety and efficacy of HES in perioperative non-septic patients (86). Several smaller studies and RCTs in non-septic patients in the perioperative setting found no evidence of a nephrotoxic effect of HES (87,88). Likewise, two recent larger, multicenter trials in 4,545 ("RaFTinG" in 2018) and 775 ("FLASH" in 2020) surgical patients also found no significant difference in mortality between patients who received HES or crystalloids and AKI in one (89), and according to the authors a reduced risk of RRT and AKI in another (90) (Supplementary Table 1).…”
Section: Acute Kidney Injury and Mortalitymentioning
confidence: 99%
“…In critically ill humans, HES exposure has been linked to an increased incidence of AKI and the need for renal replacement therapy, particularly in patients affected by sepsis or burns, whereas studies conducted in patients undergoing surgery have reported contrasting results [ 7 , 21 , 22 , 23 , 24 , 25 , 26 ]. Datzmann et al assessed some functional renal parameters and structural biomarkers (including NGAL) in people undergoing coronary bypass grafting without showing differences in mortality, acute kidney injury, the need for renal replacement therapy, or evidence of a mechanism for tubular injury [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among many studies reporting no negative safety profile of HES 130/0.4 in each unique type of surgery [12,14,16,[19][20][21]33], our study covering the entire types of surgery would have a greater generalizability. The manufacturer and distributor of HES 130/0.4 in Japan funded this study.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Studies of critically ill nonsurgical patients showed that colloids, including albumin and hydroxyethyl starch (HES), were no better and sometimes less effective than crystalloids in reducing renal morbidity [6][7][8][9][10]. However, in studies of surgical patients, the newest preparation of 6% HES 130/0.4 (Voluven ® ; Fresenius Kabi GmbH, Germany) was not associated with renal damage [11][12][13][14][15][16]. A recent multicenter randomized trial for high-risk abdominal surgery compared HES 130/0.4 with crystalloid using Doppler-guided GDFT and showed no evidence of renal toxicity in patients receiving HES 130/0.4 [11].…”
Section: Introductionmentioning
confidence: 99%